Effect of Nd-YAG, XeCl, and Nitrogen Laser Radiation on Human Aorta , and Some Arterial Tissues - Al-Wattar, Abbas J. (Iraqi Journal of Physics, 2008)
The effect of laser radiation on human aorta, coronary, and pulmonary arteries, and pulmonary veins has been investigated. Xenon-Chloride (eximer), Nitrogen, and Nd-YAG pulsed lasers of wavelengths 308, 337, and 1060 nm respectively were used. Their effects on fresh postmortem tissues, normal and diseased, was studied. The diameter and depth of ablation of the exposed tissues, in air, were measured as a function of many factors related to the type of laser and nature of the tissue. The effect of properties of the applied lasers, such as average power density and deposited energy density, on the exposed tissue surface were studied. The increase of these two parameters cause an increase in the depth and diameter of ablation. However the diameter increases until it reaches a saturation value defined by the laser spot cross section. The laser effects were studied as functions of the tissues’ nature and thickness. Normal tissues were found to have higher values of ablations’ diameters and depths in comparison in with atheromatous tissues. It has been found also that the laser ablation decreases as the tissue thickness increases. It has been found that optical properties of the tissues, such as absorption coefficient, play important role in laser – tissue interaction. When the absorption increases the effects of laser increase too. Light microscopy showed that clean cuts with histological normal edges were produced when UV lasers had been applied, with no thermal effects on the tissues.